Carnosine and other imidazole-containing compounds enhance the postdenervation depolarization of the rat diaphragm fibres - Urazaev, A Kh; Naumenko, N V; Nikolsky, E E; Vyskocil, F (Physiological research, 1998)
In the presence of carnosine, anserine, histidine, imidazole and 7-nitro indazole, the early postdenervation depolarization of muscle of about 8 mV was significantly increased by 2.15-4.8 mV. The presence of the imidazole ring in the molecule is apparently necessary for this effect. These compounds also eliminated an NO-mediated protective effect of L-glutamate and carbachol on the depolarization of membrane potential. The presence of imidazole, 7-nitro indazole, carnosine and anserine did not significantly change the effect of an external NO donor, sodium nitroprusside. The structural and functional similarity between imidazole derivatives and the known NO synthase inhibitor, 7-nitro indazole suggests that imidazole, carnosine and anserine might act by inhibiting NO production which is stimulated by glutamate and carbachol.
Keywords: donory oxidu dusnatého; denervace svalu; Imidazoles; imidazoly; Muscle Denervation; anserin; Glutamic Acid; oxid dusnatý; synthasa oxidu dusnatého; krysa rodu Rattus; zvířata; Nitric Oxide; nitroprusid; Indazoles; potkani Wistar; Anserine; indazoly; Rats, Wistar; Male; karnosin; bránice; inhibitory enzymů; Rats; Animals; Diaphragm; Membrane Potentials; Nitric Oxide Donors; mužské pohlaví; membránové potenciály; Nitroprusside; Enzyme Inhibitors; Nitric Oxide Synthase; Carnosine; kyselina glutamová